2003
DOI: 10.1124/mol.64.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid (AMPA) Receptors Facilitates Use-Dependent Inhibition by Pentobarbital

Abstract: Although the mechanisms underlying the use-dependent inhibition of ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) by barbiturates are not well understood, it has generally been assumed to involve open channel block. We examined the properties of the inhibition of AMPARs by the barbiturate pentobarbital (PB) in acutely isolated and cultured hippocampal neurons. PB caused a use-and concentration-dependent inhibition (IC 50 ϭ 20.7 M) of AMPAR-mediated currents evoked by kainate. Contrary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…[120][121][122] Unlike GABA A receptors and NMDA receptors, the AMPA and kainite subtypes of glutamate receptors are not key targets for most general anesthetics, 65,106 although barbiturates inhibit AMPA and kainate receptors. [123][124][125] Intravenous anesthetics, including etomidate, propofol, and barbiturates, enhance the GABA A receptor function, and this effect contributes to hypnosis, immobility, and memory blockade. 105,108,111,114,126,127 The halogenated volatile anesthetics (isoflurane, sevoflurane, and desflurane) also enhance GABA A receptor function, although these drugs appear to be less selective for GABA A receptors than most intravenous anesthetics.…”
Section: General Anesthetics and The Neural Substrates Of Memorymentioning
confidence: 99%
“…[120][121][122] Unlike GABA A receptors and NMDA receptors, the AMPA and kainite subtypes of glutamate receptors are not key targets for most general anesthetics, 65,106 although barbiturates inhibit AMPA and kainate receptors. [123][124][125] Intravenous anesthetics, including etomidate, propofol, and barbiturates, enhance the GABA A receptor function, and this effect contributes to hypnosis, immobility, and memory blockade. 105,108,111,114,126,127 The halogenated volatile anesthetics (isoflurane, sevoflurane, and desflurane) also enhance GABA A receptor function, although these drugs appear to be less selective for GABA A receptors than most intravenous anesthetics.…”
Section: General Anesthetics and The Neural Substrates Of Memorymentioning
confidence: 99%
“…A high degree of non-stationarity is not surprising given the time course of glutamate concentration in the synapse, which rises very quickly and decays in a multi-exponential manner, though more slowly (Clements 1996;Glavinović and Rabie 1998), and the concentration dependence of several rates of the kinetic scheme of AMPA channels (Colquhoun et al 1992). Moreover, the desensitization of AMPA receptors, which develops rapidly during the time course of unitary excitatory post-synaptic currents, contributes significantly to shaping the time course of mEPSCs (Jones and Westbrook 1996;Glavinović and Rabie 1998;Hirasawa et al 2001;Wall et al 2002;Jackson et al 2003;Yelshansky et al 2004). The gating mechanism of transmitter-activated channels, such as ACh and AMPA channels are complex (Katz and Thesleff 1957;Trussell and Fischbach 1989), and their desensitization is associated with a progressively changing pattern of bursts and clusters (Sakmann et al 1980), which renders the spectra of their current fluctuations non-stationary, even when activated by constant and spatially uniform pulses of transmitter (Aristizabal and Glavinović 2003).…”
Section: Introductionmentioning
confidence: 94%
“…A study in cultured cortical neurons revealed that the inhibition of AMPA-type receptor channels by pentobarbital is use dependent, an effect interpreted as being consistent with an open-channel block mechanism [32] . However, another study suggests that pentobarbital does not act as an openchannel blocker of AMPA-type receptor channels [33] . Rather, the sensitivity, use dependence and trapping of inhibition by pentobarbital are determined by AMPA-type receptor channel desensitization [33] .…”
Section: Phenobarbitalmentioning
confidence: 99%
“…However, another study suggests that pentobarbital does not act as an openchannel blocker of AMPA-type receptor channels [33] . Rather, the sensitivity, use dependence and trapping of inhibition by pentobarbital are determined by AMPA-type receptor channel desensitization [33] . From our results, the block mechanism of phenobarbital on AMPA-type receptor channels seems to be a combination of an openchannel block and an additional competitive-block effect.…”
Section: Phenobarbitalmentioning
confidence: 99%